2020
DOI: 10.3390/ijerph17186643
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties, Fear and Stigma: Perceptions of Zika Virus among Pregnant Women in Spain

Abstract: Similar to other epidemics, knowledge about Zika virus (ZIKV) relies upon information often coming from outside the health system. This study aimed to explore views, perceptions and attitudes towards ZIKV among migrant women from Central and South America, diagnosed with ZIKV infection during pregnancy, and to comprehend healthcare professionals’ perceptions of ZIKV. An exploratory qualitative study, based on phenomenology and grounded theory, was conducted in Barcelona, Spain. Data were collected through in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…Participants were identified from a surveillance study of ZIKV during pregnancy conducted at the Department of Maternal-Fetal Medicine, BCNatal-Barcelona Center of Maternal-Fetal and Neonatal Medicine, Hospital Clínic (HCB) and Hospital Sant Joan de Déu (HSJD). Study participants were women who had been diagnosed with ZIKV infection (confirmed or probable cases) during pregnancy, and a subset of healthcare professionals who assisted them during pregnancy and childcare [ 7 ]. In Colombia, the study was performed between April and July 2019.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were identified from a surveillance study of ZIKV during pregnancy conducted at the Department of Maternal-Fetal Medicine, BCNatal-Barcelona Center of Maternal-Fetal and Neonatal Medicine, Hospital Clínic (HCB) and Hospital Sant Joan de Déu (HSJD). Study participants were women who had been diagnosed with ZIKV infection (confirmed or probable cases) during pregnancy, and a subset of healthcare professionals who assisted them during pregnancy and childcare [ 7 ]. In Colombia, the study was performed between April and July 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The whole spectrum of the consequences of the epidemics cannot be explained just from a clinical or epidemiological view. In turn, interdisciplinarity is essential to understand the toll of carrying a child with ZIKV-related disabilities; the mental health of populations affected by ZIKV, especially of caregivers of children with disabilities, suffering during pregnancy for uncertainties regarding to child health; socio-economic impoverishment due to special care needs; and ZIKV-associated stigma [ 6 , 7 ]. Studies addressing the socio-economic impact of the ZIKV infection among affected families are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These pregnant adolescents are especially vulnerable to access appropriate health care services, including fewer antenatal care visits compared to adult pregnant women and resulting in poorer maternal and child health [ 25 ]. The importance of a prompt diagnosis of arboviral infection during pregnancy lies on the psychosocial impact it has for affected women’s mental health and emotional state [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%